PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THE LEARNING CELL UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN (KSP) DI KELAS XI SMAN 2 PEKANBARU - Sri Rahayu Lestari; Herdini '; Roza Linda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research about the learning cell type of cooperative learning model has been conducted in SMAN 2 Pekanbaru. The purpose of this research is to improve the student achievement on the topic solubility and constant solubility product (Kelarutan dan Hasil Kali Kelarutan Ksp) in class XI SMAN 2 Pekanbaru. The type of this research is experimental research with experiment design randomized control group pretest-posttest. Sample of the research consisted of two classes, a class XI MIA2 as an experimental class (implemented the learning cell type of cooperative learning model) and class XI MIA1 as the control class (without the learning cell type of cooperative learning model). T-test was used as analysis technique. Based on the data analysis obtained t > t table i.e 3.63 > 1.66, meaning that the application of the learning cell type of cooperative learning model can improve the student achievement on the subject solubility and constant solubility product (Ksp) in class XI SMA Negeri 2 Pekanbaru. The improvement of the student achievement category (N-Gain) as high as 0.82.Keywords: Student Achievement, The Leraning Cell Type Of Cooperative Learning Model, solubility and constant solubility product (Ksp).